Karol V: Cesarz z ludzką twarzą. Uwagi na marginesie książki Henry’ego Kamena, Carlos Emperador. Vida del rey césar, trad. del inglés de Paz Pruneda, La Esfera de los Libros, Madrid 2017, ss. 465 - Kubiaczyk, Filip (Studia Europaea Gnesnensia, 2019)
In this paper, the author undertakes a critical analysis of the findings relat-ing to the life and reign of Charles V, contained in the monarch’s biography by the English historian Henry Kamen. Particular attention is paid here to those elements of biographical narrative in which Kamen does not go beyond the established interpretive canon (as in the case of the imperial election of 1519 and rivalry with Francis I), those which go against predominant views (e.g. the question of the Reformation or Charles’ relationship with his mother), as well as the most controversial assertions (American policy, for instance). The chief intention of the author, who confronts the findings and the opinions expressed by Kamen with the interpretations of other researchers, is to address and fill some of the gaps in the Polish discourse concerning Charles V, where the es-tablished stereotypes surrounding the emperor continue to the iterated.